2019
DOI: 10.1177/1947603519893076
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Restoration of Patellofemoral Lesions: A Systematic Review

Abstract: Purpose This study aimed to systematically analyze the postoperative clinical, functional, and imaging outcomes, complications, reoperations, and failures following patellofemoral cartilage restoration surgery. Methods This review was conducted according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PubMed, EMBASE, and Cochrane Library databases were searched up to August 31, 2018, to identify clinical studies that assessed surgical outcomes of patellofemoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 75 publications
(312 reference statements)
0
16
0
1
Order By: Relevance
“…One possible explanation is that the majority of patients included in the Mirzayan et al study were primarily treated for patellar instability, whereas the patients in the present study were treated primarily for degenerative change; this could lead to differences in both the type of chondral injury and biological healing response. In a recent systematic review, Andrade et al 1 showed that when compared with osteochondral autograft transfer, autologous chondrocyte implantation, particulated juvenile allograft cartilage, and autologous matrix-induced chondrogenesis, OCA of the patella led to similar improvements in clinical scores above the MCID, with no definitive differences between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the majority of patients included in the Mirzayan et al study were primarily treated for patellar instability, whereas the patients in the present study were treated primarily for degenerative change; this could lead to differences in both the type of chondral injury and biological healing response. In a recent systematic review, Andrade et al 1 showed that when compared with osteochondral autograft transfer, autologous chondrocyte implantation, particulated juvenile allograft cartilage, and autologous matrix-induced chondrogenesis, OCA of the patella led to similar improvements in clinical scores above the MCID, with no definitive differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…4,27 Although most of the existing outcomes literature has focused on condylar OCA, treatment of patellar lesions with OCA has been reported as well. Patellar OCA has been shown to have good outcomes, comparable with other forms of cartilage restoration in the patella, 1 with graft survivorship of 78.1% at both 5 and 10 years, maintained improvement in pain and function, and 89% patient satisfaction. 9 The unique shape of the patella presents a challenge for osteochondral allograft implantation.…”
mentioning
confidence: 92%
“…Hence, it is suggested that OCA be reserved for salvage and revision situations. [82] The medial and lateral trochlea which are the usual donors for OATS can be used in these cases for only small patellar defects. Scaffolds for patellar cartilage regeneration have given disappointing results with a 90% failure and 70% re-operation rate.…”
Section: Patellofemoral Jointmentioning
confidence: 99%
“…Going forward scaffolds with better stress resistance need to be developed. [82] Algorithmic approach to recurrent lateral patellar instability…”
Section: Patellofemoral Jointmentioning
confidence: 99%
“…Patellar eklem kaybı patella baja ve patellar eklem kontraktüründe daha yaygın görülmektedir (Şekil 1). [6]…”
Section: Patello-femoral Hizalamanın Kıkırdak Lezyonlarına Etkisiunclassified